In conversation with Alfred Brendel - Oscar Caravaca Gonzalez (Epistemus)
Alfred Brendel holds a prominent place among the great pianists of the 20th and 21st centuries, being recognized not only for his acclaimed performances, but also for his significant contributions as a thinker, poet, and lecturer. This paper aims to share a question-and-answer session between Alfred Brendel and Óscar Caravaca, which took place during his lecture on January 31, 2018 in Mallorca, Spain. The reflections shared here illuminate the continuing tension between the performer's moral responsibility to honor the composer's intentions and the desire for personal artistic expression.